Karaktristik Perempuan Minangkabau dalam Kaba Siti Kalasum Karya Syamsudin St. Radjo Endah - Desmaliza, Desmaliza; Nst., Bakhtaruddin; Hamidin, Hamidin (Universitas Negeri Padang, 2013)
The purpose of the study was to describe (1) the characteristics of women as individuals, (2) the characteristics of women as members of society. The research data was characteristic of Minangkabau women in kaba siti kalasun. The source of the research data was obtained from kaba siti kalasun itself. Data were collected by using a descriptive method that promotes appreciation of the interaction between concepts studied empirically. The research findings were characteristic of Minangkabau women in kaba siti kalasun as follows: female characteristics as a person: having the nature of love, the nature of patient, gentle nature, and life orientation, and characteristics of women as members of society: the relationship with the environment/other people and have a concern environment/others.